Testing and application of a refined rapid detection method for paralytic shellfish poisoning toxins in UK shellfish. (15th June 2015) - Turner, Andrew D.; Tarnovius, Sophie; Johnson, Sarah; Higman, Wendy A.; Algoet, Myriam
Abstract: The Scotia Rapid Test for PSP is designed for qualitative identification of saxitoxins at levels in shellfish equivalent to the limit of detection of the biological reference method. However, issues with the method have been reported, including the low assay cross reactivity for some toxins, high numbers of false positive results and the subjective test interpretation. This study focussed on approaches to improve each of these issues. A refined test was found to improve GTX1&4 test sensitivity in samples containing high proportions of GTX1&4. The subjectivity of the test was successfully eliminated through use of an automated scanner, which enabled both the reliable identification of test results as well as the provision of a numerical result which could be utilised for more refined results interpretation. Finally the high proportion of false positive results in comparison with the LC-FLD was investigated, with a modified approach incorporating an additional extract dilution applied to a range of shellfish samples with different toxicities. Results showed highly variable limits of detection of the method and no significant reduction in false positive results when applying the additional dilution, which may be of concern to laboratories in receipt of high numbers of samples containing low concentrations of toxins. Highlights: Refined lateral flow assay. Tested on standards and samples. Increased sensitivity for GTX14. Improved detection in shellfish. Automated results interpretation.